Bello : internacionalista y «anticipacionista» - Cave Schnöhr, Rose (Estudios Internacionales, 2006)
Although part of the work of Andrés Bello, a Venezuelan intellectual who arrived in Chile in 1829, is now obsolete, other topics dealt with by him retain all their relevance or an anticipation of principles of international law that are widely recognize and accepted these days, as are the principle of solidarity, equality of States and individuals, non-intervention, State responsibility and protection of its nationals, the concept of the common heritage of humanity, marine spaces , the law of treaties, the peaceful settlement of disputes, among other important contributions. In this paper, his legacy in this matter is detailed from the review of two editions of the same work, first appearing as Principles of the Law of Peoples and then as Principles of International Law.